Apical root canal anatomy in the mesiobuccal root of maxillary first molars: influence of root apical shape and prevalence of apical foramina – a micro‐CT study. (28th March 2019) - Ordinola‐Zapata, R.; Martins, J. N. R.; Niemczyk, S.; Bramante, C. M.
Abstract: Aim: To determine whether a relationship exists between the apical shape of roots and root canal system complexity by performing a micro‐computed tomography analysis. Methodology: One hundred extracted permanent maxillary first molars were scanned using a micro‐computed tomography device at 19.6 μm voxel size. Two groups of mesiobuccal roots were formed according to the root aspect ratio value in the apical 3‐mm cross‐sectional level ('<2 and ≥ 2.00'). Data were recorded regarding the number and presence of accessory canals and their location, isthmus, presence of the mesiobuccal canal and dentine thickness. Depending on the analysed variable, Mann–Whitney U test and Z ‐test for proportions were used to compare groups. The significant level was set at 5%. Results: Mesiobuccal roots with an aspect ratio ≥ 2.00 at the apical 3‐mm cross‐sectional level had higher percentages of accessory canals, apical foramina and MB2 root canals in the apical 3 mm. The vertical average distance from the accessory foramina and origin from the anatomic apex was 1.40 and 2.19 mm, respectively. Overall, 21.8% of the accessory canals had their origin coronal to a 3‐mm root resection line. There was no difference between the groups regarding dentine thickness. Conclusion: The shape of the apical 3 mm of maxillary first molar mesiobuccal roots was a predictive factor for the presence of complex root canal systems. Roots with a lower aspect ratio had less complex apical anatomy.